Dislocation scatterings in p-type Si1−xGex under weak electric field. (16th November 2015) - Hur, Ji-Hyun; Jeon, Sanghun
Abstract: We present a theoretical model which describes hole mobility degradation by charged dislocations in p-type Si1− x Ge x . The complete analytical expression of the dislocation mobility is calculated from the momentum relaxation time of hole carriers under weak electric field. The obtained dislocation mobility shows a T 3/2 / λ relation and is proportional to the germanium density x . We also suggest a criterion for negating scatterings by dislocations in terms of the controllable parameters such as acceptor dopant density, dislocation density, temperature, and Ge density x, etc.